Autoimmune encephalitis followed by hemophagocytic lymph histiocytosis: a case report - Huang, Li; Tan, Jie; Lin, Peihao; Chen, Zixuan; Huang, Qihua; Yao, Haiyan; Jiang, Lihong; Long, Baoyi; Long, Youming (Frontiers in Immunology, 2024)
Objective This study aims to report three cases of autoimmune encephalitis followed by hemophagocytic lymphohistiocytosis. Methods Data of relevant patients treated between 2019 and 2022 were retrospectively collected from the Department of Neurology at the Second Affiliated Hospital of Guangzhou Medical University. Results The age at onset of the three patients was 37, 63, and 36 years, respectively. All three patients were female and presented with cognitive dysfunction and seizures. Behavioral and psychological symptoms were also observed in two cases. All patients were positive for autoantibodies in both the cerebrospinal fluid and serum, while two showed multiple abnormal brain signals on magnetic resonance imaging. All patients exhibited hypocytosis and elevated soluble CD25 and serum ferritin levels. The final diagnoses in two cases were lymphomas, while the remaining case without tumors suffered from a severe infection. All patients received immunotherapy, and the two with lymphoma received anti-tumor treatment. The patient with infection died, and two patients with tumors improved after chemotherapy. Conclusion Autoimmune encephalitis followed by hemophagocytic lymphohistiocytosis is a rare and severe condition. Prompt attention should be paid to the decline in blood cell counts, particularly in patients who show a slight improvement after immunotherapy or have a risk of lymphoma. Screening for potential tumors and infections and early treatment may help these patients.